Glaciers and Global Warming - Koerner, Roy; Lundgaard, Leif (Géographie physique et Quaternaire, 1995)
ABSTRACTIce core and mass balance studies from glaciers, ice caps and ice sheets constitute an ideal medium for monitoring and studying present and past environmental change and, as such, make a valuable contribution to the present debate over anthropogenic forcing of climate. Data derived from 32 years of measurements in the Canadian Arctic show no significant trends in glacier mass balance, ice melt, or snow accumulation, although the mass balance continues to be slightly negative. Models suggest that industrial aerosol loading of the atmosphere should add to the warming effect of greenhouse gases. However, we have found a sharp increase in the concentration of industrial pollutants in snow deposited since the early 1950's which makes the trendless nature of our various time series surprising. Spatial differences in the nature of climatic change may account for the lack of trend in the Queen Elizabeth Islands but encourages similar investigations to this study elsewhere in the circumpolar region. A global warming trend over the past 150 years has been demonstrated from instrumental data and is evident in our ice cores. However, the ice core data and glacier geometry changes in the Canadian Arctic suggest the Arctic warming is more pronounced in summer than winter. The same warming trend is not unique when viewed in the context of changes over the past 10,000 or 100,000 years. This suggests the 150-year trend is part of the natural climate variability.